2022
DOI: 10.3390/app12031473
|View full text |Cite
|
Sign up to set email alerts
|

Techniques, Tricks, and Stratagems of Oral Cavity Computed Tomography and Magnetic Resonance Imaging

Abstract: The oral cavity constitutes a complex anatomical area that can be affected by many developmental, inflammatory, and tumoural diseases. MultiSlice Computed Tomography (MSCT) and Magnetic Resonance Imaging (MRI) currently represent the essential and complementary imaging techniques for detecting oral cavity abnormalities. Advanced MRI with diffusion-weighted imaging (DWI) and dynamic contrast-enhanced perfusion-weighted imaging (DCE-PWI) has recently increased the ability to characterise oral lesions and disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…The authors found that positron emission tomography/CT showed higher sensitivity, specificity, positive predictive value, and negative predictive value than did the two other modalities, making it an important diagnostic tool in the preoperative staging of squamous cell carcinoma of the oral cavity. According to Maraghelli et al ( 35 ) , multislice CT and MRI are fundamental and complementary in the study and observation of oral infiltration by cavitary diseases, whereas ultrasound and cone-beam CT still play only a marginal role. They also concluded that although positron-emission tomography with fluorine-18-fluorodeoxyglucose does not allow a morphological evaluation like multislice CT and MRI, it is useful in detecting oral neoplasms that are undetectable on conventional imaging, lymph node metastases, other distant metastases, and post-radiotherapy recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that positron emission tomography/CT showed higher sensitivity, specificity, positive predictive value, and negative predictive value than did the two other modalities, making it an important diagnostic tool in the preoperative staging of squamous cell carcinoma of the oral cavity. According to Maraghelli et al ( 35 ) , multislice CT and MRI are fundamental and complementary in the study and observation of oral infiltration by cavitary diseases, whereas ultrasound and cone-beam CT still play only a marginal role. They also concluded that although positron-emission tomography with fluorine-18-fluorodeoxyglucose does not allow a morphological evaluation like multislice CT and MRI, it is useful in detecting oral neoplasms that are undetectable on conventional imaging, lymph node metastases, other distant metastases, and post-radiotherapy recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Puffed cheek technique improves the contour and margin delineation as compared to the conventional CECT. 23 Also, this technique separates the mucosal surface from alveolus enabling better assessment of subtle lesions that may otherwise be missed in routine imaging. With puffed cheek technique structures like buccal mucosa, gingival, buccal vestibule and RMT are better delineated ( Fig.…”
Section: Imaging Guidelinesmentioning
confidence: 99%
“…DCE-PWI is crucial in the detection of focal lesions since it mainly assesses the vascular permeability [23]. Changes in hemodynamic parameters can precede abnormalities on conventional MRI and can thus be used to help with the diagnosis [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%